Sedimentology, chemostratigraphy and stromatolites of lower Paleoproterozoic carbonates, Turee Creek Group, Western Australia. - Mazumder, Rajat; Martindale. R.; Strauss, J.; Sperling, E.; Johnson, J.; Van Kranendonk, M.; Flannery, D.; French, K.; Mazumder, Rajat (Elsevier BV, 2015)
The ca. 2.45–2.22 Ga Turee Creek Group, Western Australia, contains carbonate-rich horizons that postdate earliest Proterozoic iron formations, bracket both Paleoproterozoic glaciogenic beds and the onset of the Great Oxidation Event (GOE), and predate ca. 2.2–2.05 Ga Lomagundi-Jatuli C-isotopic excursion(s). As such, Turee Creek carbonate strata provide an opportunity to characterize early Paleoproterozoic carbonate sedimentation and carbon cycle dynamics in the context of significant global change. Here, we report on the stratigraphy, sedimentology, petrology, carbon isotope chemostratigraphy, and stromatolite development for carbonate-rich successions within the pre-glacial part of the Kungarra Formation and the postglacial Kazput Formation. Kungarra carbonate units largely occur as laterally discontinuous beds within a thick, predominantly siliciclastic shelf deposit. While this succession contains thin microbialite horizons, most carbonates consist of patchy calcite overgrowths within a siliciclastic matrix. C-isotopic values show marked variation along a single horizon and even within hand samples, reflecting spatially and temporally variable mixing between dissolved inorganic carbon in seawater and isotopically light inorganic carbon generated via syn- and post-depositional remineralization of organic matter.In contrast, the Kazput carbonates consist of subtidal stromatolites, grainstones, and micrites deposited on a mixed carbonate–siliciclastic shelf. These carbonates exhibit moderate δ13C values of −2‰ to +1.5‰ and likely preserve a C-isotopic signature of seawater. Kazput carbonates, thus, provide some of the best available evidence that an interval of unexceptional C-isotopic values separates the Lomagundi-Jatuli C-isotopic excursion(s) from the initiation of the GOE as inferred from multiple sulfur isotopes (loss of mass independent fractionation). The Kazput Formation also contains unusual, m-scale stromatolitic buildups, which are composed of sub-mm laminae and discontinuous, convex upward lenticular precipitates up to a few mm in maximum thickness. Laminae, interpreted as microbial mat layers, contain quartz and clay minerals as well as calcite, whereas precipitate lenses consist of interlocking calcite anhedra, sometimes showing faint mm-scale banding. These cements formed either as infillings of primary voids formed by gas emission within penecontemporaneously lithified mats, or as local seafloor precipitates that formed on, or within, surface mats. It is possible that both mechanisms interacted to form the unique Kazput stromatolites. These microbialites speak to a distinctive interaction between life and environment early in the Paleoproterozoic Era.